Persepsi Atlet terhadap Peran Pelatih dalam Pembinaan Dancesport Kabupaten Bantul - Dimas Yoga Pratama; Agus Pribadi; Bimo Alexander; Andri Arif Kustiawan (MAN Insan Cendekia Jambi, 2026)
The coach plays a crucial role in athlete development, particularly in dancesport, which requires technical mastery, physical fitness, psychological readiness, and effective communication between coaches and athletes. This study aimed to describe the role of coaches in improving the performance of dancesport athletes at the Indonesian Dancesport Association (IODI) of Bantul Regency. A descriptive quantitative method was employed using a total sampling technique. The participants consisted of 20 active athletes aged 13–15 years. Data were collected using a Likert-scale questionnaire that had met validity and reliability requirements (Cronbach's Alpha = 0.833). Data were analyzed using descriptive statistics, including mean scores, percentages, and Norm-Referenced Assessment (PAN). The findings indicated that the coach's role was categorized as influential (45%) and moderately influential (35%), with a mean score of 53. Among the five indicators, training implementation achieved the highest percentage (91.7%), followed by motivation (90.0%), communication (89.6%), training program planning (86.9%), and evaluation (85.9%). These findings indicate that coaches have effectively performed their roles in planning, implementing, motivating, evaluating, and communicating during the athlete development process, thereby supporting the improvement of dancesport athlete performance in Bantul Regency.